2020
DOI: 10.3758/s13415-020-00779-4
|View full text |Cite
|
Sign up to set email alerts
|

Your losses are mine: The influence of empathic concern on evaluative processing of others’ outcomes

Abstract: Neural responses to others' decision-making outcomes can be modulated by many social factors. Using the event-related potential (ERP) technique, we explored the neural mechanisms of empathic concern modulating evaluative processing of others' outcomes. Participants were asked to perform a gambling task for three beneficiaries: themselves and two strangers. One stranger was an economically underprivileged student requiring help (high-empathy condition); the other stranger was a student with no upsetting informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 80 publications
(127 reference statements)
3
16
0
1
Order By: Relevance
“…1 引言 共情作为一种深入感受和理解他人情绪的能 力 (Decety & Lamm, 2006), 受到了广泛的关注和研 究。随着研究的深入, 研究者提出共情能够对决策 产生影响, 并且这一观点得到了来自问卷调研、行 为实验和电生理研究等多角度的科学验证。根据共 情−利他假说(empathy-altruism hypothesis): 当他人 陷入困境时, 个体会产生一系列包括共情关怀、同 情、怜悯的情绪并且产生解除其困境的利他动机, 从而采取利他行为 (Batson, 1991;Batson & Shaw, 1991)。因此, 研究者们重点探讨了共情对利他决策 的影响 (FeldmanHall et al, 2015;McAuliffe et al, 2018;Liu et al, 2018Liu et al, , 2020 出不公平厌恶现象 (Fehr & Schmidt, 1999), 体现为 不公平引发的消极情绪以及以牺牲自身利益为代价 拒绝不公平分配的行为 (Camerer, 2003;Polezzi et al, 2008;Sanfey et al, 2003) (Batson et al, 2007), 同时个体也注重 公平, 甚至不惜牺牲自身利益以惩罚不公平 (Camerer, 2003;Fehr & Gachter, 2002) (Bradley et al, 2001;Hewig et al, 2011;Hu & Mai, 2021), 其中"5"表示心情平静与温和; 从"5"到"9" 表示积极的情绪体验, 从"5"到"1"表示消极的情绪 体验, 程度越来越强烈。公平感知评定采用 7 点计 分 (Leliveld et al, 2012;Pillutla & Murnighan, 1996),…”
unclassified
“…1 引言 共情作为一种深入感受和理解他人情绪的能 力 (Decety & Lamm, 2006), 受到了广泛的关注和研 究。随着研究的深入, 研究者提出共情能够对决策 产生影响, 并且这一观点得到了来自问卷调研、行 为实验和电生理研究等多角度的科学验证。根据共 情−利他假说(empathy-altruism hypothesis): 当他人 陷入困境时, 个体会产生一系列包括共情关怀、同 情、怜悯的情绪并且产生解除其困境的利他动机, 从而采取利他行为 (Batson, 1991;Batson & Shaw, 1991)。因此, 研究者们重点探讨了共情对利他决策 的影响 (FeldmanHall et al, 2015;McAuliffe et al, 2018;Liu et al, 2018Liu et al, , 2020 出不公平厌恶现象 (Fehr & Schmidt, 1999), 体现为 不公平引发的消极情绪以及以牺牲自身利益为代价 拒绝不公平分配的行为 (Camerer, 2003;Polezzi et al, 2008;Sanfey et al, 2003) (Batson et al, 2007), 同时个体也注重 公平, 甚至不惜牺牲自身利益以惩罚不公平 (Camerer, 2003;Fehr & Gachter, 2002) (Bradley et al, 2001;Hewig et al, 2011;Hu & Mai, 2021), 其中"5"表示心情平静与温和; 从"5"到"9" 表示积极的情绪体验, 从"5"到"1"表示消极的情绪 体验, 程度越来越强烈。公平感知评定采用 7 点计 分 (Leliveld et al, 2012;Pillutla & Murnighan, 1996),…”
unclassified
“…This subtle process may enhance disparities that emerge between different social roles. Second, several studies have confirmed that situational induced empathy affects an individual's altruistic behavior (Liu et al, 2020), while the relationship with fairness perception remains unclear. These results have noteworthy theoretical significance for recent advancements in state empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Fairness is an important concept in human social behavior and a crucial factor in social stability (Liu, Hu, Shi, & Mai, 2020;Zhou & Wu, 2011). Numerous experimental studies have demonstrated that people who tend to pursue fairness, demand a fair distribution of wealth, are willing to punish individuals who behave unfairly (Batson & Shaw, 1991;Camerer, 2011;Fehr & Schmidt, 2006;Waal, 2008) and may even loathe those who take advantage of others (de Hooge, Nelissen, Breugelmans, & Zeelenberg, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies (e.g., Hu et al, 2017;Liu et al, 2020;Marco-Pallarés et al, 2010;Rigoni et al, 2010;Qi et al, 2018;Wu et al, 2012;Zhang et al, 2020Zhang et al, , 2021 and visual inspection of grand waveforms, ERPs were quantified using the mean amplitudes for P200 (190-260 ms), RewP (290-360 ms), P300 (360-420 ms) and LPP (420-750 ms) components. The P200 and RewP components were measured at the Fz and FCz electrodes.…”
Section: Eeg Recordings and Pre-processingmentioning
confidence: 99%
“…Moreover, several studies have presented both selfrelated and others' outcomes, suggesting that these two outcomes interact with each other (e.g., Boksem et al, 2011;Hu et al, 2017;Liu et al, 2020;Marco-Pallarés et al, 2010;Rigoni et al, 2010;Qi et al, 2018;Wu et al, 2012;Zhang et al, 2020Zhang et al, , 2021. For example, Rigoni and colleagues (2010) reported that the P200 component was larger in amplitude for self-related gains than for selfrelated losses when participants were only presented with their own outcome, whereas the difference was reduced when both participants' own outcomes and the outcomes of other individuals were presented.…”
Section: Introductionmentioning
confidence: 99%